Novel mutations in GJB1 trigger intracellular aggregation and stress granule formation in X-linked Charcot-Marie-Tooth Disease - Fan Chu; Jiaming Xu; Yong Wang; Yingjie Li; Yaling Wang; Zhijun Liu; Chuanzhou Li (Frontiers in Neuroscience, 2022)
X-linked Charcot-Marie-Tooth Disease type 1(CMT1X) is the second most common form of inherited peripheral neuropathy that is caused by mutations in the gap junction beta-1 (GJB1) gene. Using targeted exome-sequencing, we investigated four CMT families from central-southern China and identified two novel missense variants (p.F31S and p.W44G) and two previously reported variants (p.R220Pfs*23 and p.Y157H) of GJB1. All four probands presented typical early-onset peripheral neuropathy, of which the R220Pfs*23 carrier also had neurologic manifestations in the central nervous system. We then constructed GJB1 expression vectors and performed cell biological analysis in vitro. Expression of FLAG-tagged GJB1 at various time points after transfection revealed evident protein aggregation with both wild-type and mutant forms, indicated with immunostaining and immunoblotting. Detergent-based sequential fractionation confirmed that all mutants were higher expressed and more prone to aggregate than the wild-type, whereas the R220Pfs*23 mutant showed the greatest amount of SDS-soluble multimers and monomers among groups. Moreover, intracellular aggregation probably occurs in the endoplasmic reticulum compartment rather than the Golgi apparatus. Gap junction plaques were present in all groups and were only compromised in frameshift mutant. Further evidence reveals significant intracellular stress granule formation induced by mutated GJB1 and impaired cell viability indicative of cytotoxicity of self-aggregates. Together, our findings demonstrate novel GJB1 variants-induced cell stress and dysfunction and provide insights into understanding the pathomechanisms of GJB1-CMTX1 and other related disorders.